Predictors of liver fat among children and adolescents from five different ethnic groups. (9th October 2020) - Maskarinec, Gertraud; Garber, Andrea K.; Wong, Michael C.; Kelly, Nisa; Kazemi, Leila; Buchthal, Steven D.; Fearnbach, Nicole; Heymsfield, Steven B.; Shepherd, John A.
Abstract: Objectives: As rates of obesity around the world have increased, so has the detection of high level of liver fat in children and adolescents. This may put them at risk for cardiovascular disease later in life. This analysis of a cross‐sectional population‐based study of children and adolescents evaluated demographic and lifestyle determinants of percent liver fat. Methods: Healthy participants (123 girls and 99 boys aged 5–17 years) recruited by convenience sampling in three locations completed questionnaires, anthropometric measurements, and dual X‐ray absorptiometry and magnetic resonance imaging (MRI) assessment. General linear models were applied to estimate the association of demographic, anthropometric, and dietary factors as well as physical activity with MRI‐based percent liver fat. Results: The strongest predictor of liver fat was body mass index (BMI; p < 0.0001); overweight and obesity were associated with 0.5% and 1% higher liver fat levels. The respective adjusted mean percent values were 2.9 (95% CI 2.7, 3.1) and 3.4 (95% CI 3.2, 3.6) as compared to normal weight (2.4; 95% CI 2.3, 2.6). Mean percent liver fat was highest in Whites and African Americans, intermediate in Hispanic, and lowest among Asians and Native Hawaiians/Pacific Islanders ( p < 0.0001). Age ( p = 0.67), sex ( p = 0.28), physical activity ( p = 0.74), and diet quality ( p = 0.70) were not significantly related with liver fat. Conclusions: This study in multiethnic children and adolescents confirms the strong relationship of BMI with percent liver fat even in a population with low liver fat levels without detecting an association with age, sex, and dietary or physical activity patterns.